Financial Organization and Operations of the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This pamphlet describes the financial structure and operations of the IMF, as well as the sources of IMF financing, the policies associated with the use of IMF resources, the role of the IMF as trustee to various accounts that are administered by it, and the safeguards established for protecting the IMF's resources. Published in 1990. Extensively revised in 2001 (sixth edition).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet